Conversation and Language Acquisition: A Pragmatic Approach. Issue 3 (3rd July 2018) - Clark, Eve V.
ABSTRACT: Children acquire language in conversation. This is where they are exposed to the community language by more expert speakers. This exposure is effectively governed by adult reliance on pragmatic principles in conversation: Cooperation, Conventionality, and Contrast. All three play a central role in speakers' use of language for communication in conversation. Exposure to language alone, however, is not enough for learning. Children need to practice what they hear, and take account of feedback on their usage. Research shows that adults offer feedback with considerable frequency when young children make errors, whether in pronunciation (phonology), in word-from (morphology), in word choice (lexicon), or in constructions (syntax). Adults also offer children new words for objects, actions, and relations. And, along with new labels for such categories, they also provide supplementary information about the referents of new words—information about parts, properties, characteristic sounds, motion, and function, as well as about related neighboring objects, actions, and relations. All this helps children build up and organize semantic domains as they learn more words and more language.